PRSPs and Budgets - Alonso, Rosa; Judge, Lindsay; Klugman, Jeni (A Synthesis of Five Case Studies, 2016)
This paper synthesizes the findings from a series of case studies on the interaction between the PRSP process and the budget. The five studies, Bolivia, Burkina Faso, Cambodia, Tanzania and Vietnam aim to assess the extent to which public finance management and budget allocations reflect the principles and content of the Poverty Reduction Strategy Paper PRSP, hence providing insights into progress in PRS implementation. The cases also shed light on whether the PRSP process itself has fostered more accountable, efficient and pro-poor budget processes and allocations as of 2003.The PRSP process, with its focus on data and information for evidence-based policy-making, open and participatory policy-making processes, poverty results and country-led donor coordination, alignment and harmonization has the potential to significantly improve the pro-poor focus and general accountability of budgeting processes.The cases confront a number of methodological challenges. First, in some countries and sectors, lack of appropriate data constrained the extent to which the research questions could be fully answered. Second, the PRSP remains a relatively recent innovation in all the countries studied and we recognize that many of our findings are preliminary, and require additional confirmation over time. Third, any assessment of the value added of the PRSP approach needs to be cognizant of the initial conditions in country, both to avoid ascribing successes to the PRSP which pre-date its existence, and to temper expectations about what the approach can deliver in a relatively short space of time given the starting point of each country. To address this last challenge, the case studies explicitly acknowledge the pre-existing situation in-country and try to assess the value added of the PRSP process.The four countries studied have a number of common features.Finally, and perhaps most importantly, all five countries share a high-level political commitment to addressing poverty, although the extent to which this commitment permeates throughout government agencies varies from country to country.The five countries, however, also display many distinctive features. Bolivia and Cambodia, for example, both suffer from high degrees of political fragmentation, which in Bolivia has manifested itself as civil unrest on a number of occasions in the last two years. Burkina Faso, Tanzania, and Vietnam, on the other hand, benefit from more stable political systems and an inherited commitment to pro-poor policies from socialist governments.